2018
DOI: 10.1111/gcb.14357
|View full text |Cite
|
Sign up to set email alerts
|

Traits drive global wood decomposition rates more than climate

Abstract: Wood decomposition is a major component of the global carbon cycle. Decomposition rates vary across climate gradients, which is thought to reflect the effects of temperature and moisture on the metabolic kinetics of decomposers. However, decomposition rates also vary with wood traits, which may reflect the influence of stoichiometry on decomposer metabolism as well as geometry relating the surface areas that decomposers colonize with the volumes they consume. In this paper, we combined metabolic and geometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 56 publications
6
53
0
Order By: Relevance
“…Furthermore, the temperature gradients present at our site (<1°C) are much smaller than gradients observed in studies that examine broad biogeographic gradients in wood decay (Adair et al, ; Bradford et al, ). Nevertheless, variation in initial wood traits more strongly influenced wood decay than environmental variability, which is consistent with global patterns (Hu et al, ; Weedon et al, ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, the temperature gradients present at our site (<1°C) are much smaller than gradients observed in studies that examine broad biogeographic gradients in wood decay (Adair et al, ; Bradford et al, ). Nevertheless, variation in initial wood traits more strongly influenced wood decay than environmental variability, which is consistent with global patterns (Hu et al, ; Weedon et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, variation in initial wood traits more strongly influenced wood decay than environmental variability, which is consistent with global patterns (Hu et al, 2018;Weedon et al, 2009).…”
Section: Trait Effects Depend On Temporal Scalesupporting
confidence: 79%
See 1 more Smart Citation
“…Leaf litter decomposability is influenced by a plant's position on the leaf economics spectrum (Díaz et al, ; Wright et al, ). In terrestrial systems, plant traits have been found to explain the decomposition rate of leaves (Cornwell et al, ) and wood (Hu et al, ) more than climatic factors. We were unable to include specific leaf traits as explanatory variables in our study due to inconsistent reporting of leaf traits in the published studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that the relationship between denser wood and slower decomposition does not hold when macrodetritivores are excluded. Other traits, such as wood nutrient concentrations, can also influence decomposition rates (Hu et al 2018). Studies in the wet tropics have shown considerable variation in wood nutrient concentrations among and within species and have indicated that these species and site-determined variables can dominate variation in decomposition rates (e.g., Heineman et al 2016).…”
Section: Discussionmentioning
confidence: 99%